Math, asked by maaz29, 1 year ago

(a^2+b^2)x^2-2 (ac+bd)x+(c^2+d^2)=0 if ad=bc

Attachments:

Answers

Answered by Anant02
1

roots \: are \: equal  \\ then \:  \\  {b}^{2}  - 4ac = 0 \\  {( - 2ac - 2bd)}^{2} - 4( {a}^{2} +  {b}^{2} )( {c}^{2} +  {d}^{2} ) = 0 \\ 4 {a}^{2}  {c}^{2}  + 4 {b}^{2}  {d}^{2}  + 8abcd - 4 {a}^{2}  {c}^{2}  - 4 {b}^{2}  {c}^{2}  - 4 {a}^{2}  {d}^{2}  - 4 {b}^{2} {d}^{2}   = 0 \\  - 4( {b}^{2} {c }^{2}  +   {a}^{2} {d}^{2}  - 2abcd) = 0 \\  {(bc - ad)}^{2}   = 0 \\ bc = ad \\
Similar questions